2015
DOI: 10.1039/c4ra15380d
|View full text |Cite
|
Sign up to set email alerts
|

A halogen- and hydrogen-bonding [2]catenane for anion recognition and sensing

Abstract: A mixed halogen- and hydrogen-bonding hetero-[2]catenane has been synthesised via anion templation and demonstrated to bind and sense oxoanions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Similarly, whereas the anion‐templated synthesis of interlocked structures has been elegantly demonstrated, most notably by Beer and co‐workers, the recognition and sensing of anions by the use of catenanes as “anion hosts” has been relatively unexplored. Most examples to date show selectivity for halide ions through halogen‐ or hydrogen‐bonding interactions within the catenane cavity ,. From the crystal structure of 3 (Figure a), it can be seen that the btp – btp units are orientated in a manner that gives rise to a highly preorganized hydrogen‐bonding environment, which can be described as being close to a “tetrahedral” arrangement.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, whereas the anion‐templated synthesis of interlocked structures has been elegantly demonstrated, most notably by Beer and co‐workers, the recognition and sensing of anions by the use of catenanes as “anion hosts” has been relatively unexplored. Most examples to date show selectivity for halide ions through halogen‐ or hydrogen‐bonding interactions within the catenane cavity ,. From the crystal structure of 3 (Figure a), it can be seen that the btp – btp units are orientated in a manner that gives rise to a highly preorganized hydrogen‐bonding environment, which can be described as being close to a “tetrahedral” arrangement.…”
Section: Methodsmentioning
confidence: 99%
“…16). 63 Addition of various anions, particularly acetate and dihydrogen phosphate, to a solution of 30•PF6 in acetonitrile caused an increase of the naphthalene monomer emission bands and the concomitant decrease in intensity of an excimer emission band. The observed sensory response was attributed to the increased rigidity reducing the number of available vibrational and rotational non-radiative decay pathways upon anion binding.…”
Section: Hb/xb Mim Host Systemsmentioning
confidence: 99%
“…Soon after, a mixed halogen and hydrogen bonding hetero[2]catenane 6 (Fig. 6) was successfully synthesized by the same group via an anion templated Grubbs’ II-catalyzed RCM clipping mechanical bond forming methodology [48]. The 1 H NMR spectroscopy in CDCl 3 (293 K, 500 MHz) and the fluorescence titration experiments which were done in acetonitrile have demonstrated that the synthesized 1,2,3-triazolium macrocycle 6 was able to bind and sense several anions but the highest affinity of this receptor was for acetate ( K a = 1.5 × 10 5 M −1 ) and dihydrogen phosphate ( K a = 4.5 × 10 4 M −1 ).…”
Section: Reviewmentioning
confidence: 99%